KONTRIBUSI HUKUM ISLAM DI INDONESIA DALAM ERA REFORMASI - ,, Mohammad Adnan; ,, Junaidi (Fakultas Hukum Universitas Sebelas Maret, 2015)
AbstractThe reform era gives many changes in the life of the Indonesian people, including in the field of law. Post- independence, the country continues to conduct development of national laws with sources include Customary law, Islamic law and Western law. The problem in this research is how the role of Islamic law play a role in the development of Indonesian law after the reform. This research is a descriptive normative. Data collection is done by means of secondary data documentation. From these results it can be seen that Islamic law has a contribution or an important role in the development of law in Indonesia, especially after the reform period. A democratic political system opens the opportunity values of Islamic law into the national legal legislative process.Keywords: Islamic Law, Reform, a national law